Inside Cover: Synthesis and Characterization of peri‐Heptacene on a Metallic Surface (Angew. Chem. Int. Ed. 23/2022). Issue 23 (5th April 2022) - Biswas, Kalyan; Urgel, José I.; Ajayakumar, M. R.; Ma, Ji; Sánchez‐Grande, Ana; Edalatmanesh, Shayan; Lauwaet, Koen; Mutombo, Pingo; Gallego, José M.; Miranda, Rodolfo; Jelínek, Pavel; Feng, Xinliang; et al.
Abstract : The precursor 4, 5, 9, 10‐tetrakis(3‐methylnaphthalen‐2‐yl)pyrene is synthesized in solution, sublimed on an Au(111) substrate under ultrahigh vacuum conditions, and converted into the peri ‐heptacene molecule by thermal activation via surface‐assisted oxidative ring‐closure and cyclodehydrogenation reactions. Details of this research can be found in the Communication by José I. Urgel, Pavel Jelínek, Xinliang Feng, David Écija, and co‐workers (e202114983 ).